2009
DOI: 10.1007/s12098-009-0196-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fetal malnutrition using “CAN score”

Abstract: CAN score identifies malnourished neonates which can be missed by other methods and identifies well nourished neonates classified as growth retarded by other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
38
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 6 publications
5
38
4
Order By: Relevance
“…In our previous study reported in 2001 about FM, 488 singleton term neonates among 3116 liveborn singleton term neonates were found to be malnourished, with an incidence of FM of 15.66% 17 . When compared with reports from Nigeria and India, the incidence of malnourished neonates in our current study is found to be strikingly lower than Nigeria (18.8%) and India (27.9–60%) 15,19,20 …”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In our previous study reported in 2001 about FM, 488 singleton term neonates among 3116 liveborn singleton term neonates were found to be malnourished, with an incidence of FM of 15.66% 17 . When compared with reports from Nigeria and India, the incidence of malnourished neonates in our current study is found to be strikingly lower than Nigeria (18.8%) and India (27.9–60%) 15,19,20 …”
Section: Discussioncontrasting
confidence: 58%
“…Studies of FM in Turkey and other countries are scarce 15–20 . Our study is one of the few studies concerning FM in liveborn singleton term neonates.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Other research has investigated perinatal outcomes using the CANSCORE to identify undernourished preterm neonates, and found that early neonatal morbidities including hypoglycemia, feeding intolerance and infection were higher in undernourished neonates compared with those appropriately grown (32). The CANSCORE is a purely clinical assessment requiring determination of physical characteristics of the newborn, thus heavily dependent on clinician or health worker skills for assessment (8). Neither the clinical assessment nor Ponderal Index methods have used a highly accurate tool to assess nutritional status such as ADP to determine sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the majority of neonatal deaths occur on the first day and within the first week after birth. Furthermore, undernourished neonates who survive are at risk of long-term health outcomes, including hypertension, stroke, type 2 diabetes, obesity, and cardiovascular disease (5)(6)(7)(8). Neonatal undernutrition, or "wasting", is a clinical diagnosis often characterized by diminished subcutaneous tissues and underlying muscles with loose wrinkled skin of the arms, legs, elbows, and knees (1,8).…”
mentioning
confidence: 99%